(untitled) - Pérez-Cerezo, Julia (Business Expert Press, 2013)
Ebook from IG Library ; China is the second-largest economy in the world, and it stands poised to become the largest. China s geopolitical power is also developing at a stunning pace. It has been predicted that China will have more impact on the world over the next 20 years than any other country. The world order as we have known it is changing, and China is becoming its leader.
Keywords: Entrepreneurship ; Small Business Management; Quản trị doanh nghiệp